PREVALENSI DAN FAKTOR RISIKO ANEMIA PADA REMAJA PUTRI DI SMAN I ABIANSEMAL BADUNG - Ni Putu Eka Febianingsih; Kadek Agus Dwija Putra; Gede Yudiana Putra (Bali Health Published Journal, 2019)
Background: High prevalence of anemia exists in the developing country where its causes are multi-factorial. One of the most vulnerable populations are adolescent girl. This study aims to know the prevalence and risk factor of anemia among adolescent girls in Abiansemal High School Methods: Cross sectional study was conduct with a total of 254 individuals comprising healthy participated. The relevant information was collected with interviews, anthropometric measurements and Hemoglobin assay. Multivariate Poisson Regression analysis was done to analysis the risk factor. Results: The prevalence of anemia was found to be 71.3% (22.8% mild anemia, 47.2% moderate anemia and 1.2% severe anemia). Mean age of the adolescent girls was 15.5 ± 0.66 years old. Multivariate analysis showed that the strongest predictors of anemia associated with adolescent girls is eating frequency ? 2 times a day (aPR:1.55; 95% CI: 1.32 to 1.81), excessive menstrual bleeding (aPR: 1, 35; 95% CI 1.17 to 1.56), vegetarian diet (aPR: 1.23; 95% CI 1.08 to 1.41) and drinking tea during meals (aPR: 1.17; 95% CI 1.01 to 1.36). However, the level of knowledge, socioeconomic status, and BMI did not contribute significantly in this study. Conclusions: High prevalence of anemia in adolescent girls of Abiansemal High School. Anemia screening should be done regularly and giving iron tablets to adolescent girls.